2015
DOI: 10.3389/fphys.2015.00077
|View full text |Cite
|
Sign up to set email alerts
|

Neural stem cells respond to stress hormones: distinguishing beneficial from detrimental stress

Abstract: Neural stem cells (NSCs), the progenitors of the nervous system, control distinct, position-specific functions and are critically involved in the maintenance of homeostasis in the brain. The responses of these cells to various stressful stimuli are shaped by genetic, epigenetic, and environmental factors via mechanisms that are age and developmental stage-dependent and still remain, to a great extent, elusive. Increasing evidence advocates for the beneficial impact of the stress response in various settings, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 146 publications
(162 reference statements)
1
17
0
Order By: Relevance
“…This is reinforced by the fact that transgenics showed increased freezing already during acquisition, suggesting that this behavior is more related to exacerbated reaction to the electric shock as stressor than to emotional learning. Thus newborn neurons seem to play a decisive role when the organism must confront novelty and complex situations, for instance, stressful events (Surget et al, ; Koutmani and Karalis, ).…”
Section: Discussionmentioning
confidence: 99%
“…This is reinforced by the fact that transgenics showed increased freezing already during acquisition, suggesting that this behavior is more related to exacerbated reaction to the electric shock as stressor than to emotional learning. Thus newborn neurons seem to play a decisive role when the organism must confront novelty and complex situations, for instance, stressful events (Surget et al, ; Koutmani and Karalis, ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study examined antenatal betamethasone administration and demonstrated that antenatal sGC therapy induces immediate hormonal alterations in the fetus 36 . Depending on the nature of the exposure, HPA function may demonstrate increased or decreased reactivity to GC 2,3,3739 . Neural stem/progenitor cells (NSPCs) are especially sensitive to increased levels of GCs, and recent evidence suggests the extent of exposure may have life-long effects on NSPCs, which ultimately shape brain development and behavior 3945 .…”
Section: Gc Metabolism and Signaling In Pregnancymentioning
confidence: 99%
“…Depending on the nature of the exposure, HPA function may demonstrate increased or decreased reactivity to GC 2,3,3739 . Neural stem/progenitor cells (NSPCs) are especially sensitive to increased levels of GCs, and recent evidence suggests the extent of exposure may have life-long effects on NSPCs, which ultimately shape brain development and behavior 3945 . It is important to recognize that many of the effects of GCs in the developing brain are necessary for proper development and have positive effects including NSPC proliferation, differentiation and survival 2,3,39 .…”
Section: Gc Metabolism and Signaling In Pregnancymentioning
confidence: 99%
“…Interestingly, ELS affects many of these same biological pathways implicated in apoptosis and neurogenesis, allostatic load, and inflammation (20,21,38). In the present study, the brain regions that showed greater contraction, or shrinking, related to severe ELS or increased PM2.5 may be experiencing accelerated cell death.…”
Section: Discussionmentioning
confidence: 52%